2019
DOI: 10.12680/balneo.2019.233
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke visual rehabilitation - the impact on life quality of the stroke survival patients - a brief review

Abstract: Visual rehabilitation therapy (VRT) is one of the most important and difficult post stroke rehabilitation component that can considerably improve the quality of patient's life. There are also evidences that VRT contribute to a better motor recuperation, by offering a support for spatial and temporal orientation due to process of motor activity recuperation. Visual rehabilitation methods can be classified into the following groups: Visual Substitution Therapy, Visual Scanning Training (VST), Audio-Visual Scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…All ISO-induced ECG AMI-like alterations mentioned above could be due to the secondary loss of action potential in the cardyomyocites, as a result of oxidative stress (13). Oxidative stress plays an important role not only in AMI but also in many other cardiovascular disorders (17)(18)(19). Younis et al reported that ISO in a dose of 85 mg/kg bw decreased in P wave, QRS complex, PR segment, and RR intervals and increased in the QT interval duration and ST-segment deviation, in comparison with the control rats (20).…”
Section: Discussionmentioning
confidence: 99%
“…All ISO-induced ECG AMI-like alterations mentioned above could be due to the secondary loss of action potential in the cardyomyocites, as a result of oxidative stress (13). Oxidative stress plays an important role not only in AMI but also in many other cardiovascular disorders (17)(18)(19). Younis et al reported that ISO in a dose of 85 mg/kg bw decreased in P wave, QRS complex, PR segment, and RR intervals and increased in the QT interval duration and ST-segment deviation, in comparison with the control rats (20).…”
Section: Discussionmentioning
confidence: 99%
“…If eye-hand coordination recovers through sensors and functional electrical stimulation, there is possibility for a more rapid progress in neurorehabilitation. A more clear characterisation of eye-hand coordination regarding the connection between ocular motor control and manual motor control will improve the understanding of its role in upper limb motor rehabilitation after stroke (31). Therefore eye-hand coordination (also known as eye-hand coupling, visuo-manual coordination or oculo-manual synergy) physiology is defined as the coordinated control of eye movements associated with the fine movements of the hands toward a given target, reaching the target and performing the desired work (32).…”
Section: Human-robotic Interface -Role In Stroke Rehabilitationmentioning
confidence: 99%
“…HH persistence is a negative predictor for patients outcome despite the motor and speech rehabilitation therapies efforts (12). It is possible that adding a systematic vision rehabilitation to other methods for stroke rehabilitation could consistently improve patient's quality of life (13,14). Many strategies that already developed in this research field of HH rehabilitation met scepticism in scientifically communities, therefore, clinical approaching was not constant followed, and there is no consensus regarding the methods and therapies applied in this form of visual disabilities.…”
Section: Introductionmentioning
confidence: 99%